Analysis of retinal nerve layers in idiopathic, LRRK2-associated Parkinson's disease and unaffected carriers of G2019S mutation. (January 2023) - Cerveró, Andrea; Sánchez-Rodríguez, Antonio; Rivera-Sánchez, María; Martínez-Rodríguez, Isabel; Sierra, María; González-Aramburu, Isabel; Gutiérrez-González, Angela; Andrés-Pacheco, Javier; Sánchez-Peláez, María Victoria; Casado, Alfonso; Infante, Jon
Abstract: Introduction: In both prodromal and early symptomatic stages of idiopathic PD (iPD) peripapillary retinal nerve fiber layer (pRNFL) and macular ganglion cell layer (mGCL) thinning have been identified. Here we assessed whether these alterations can also be detected in symptomatic and presymptomatic stages of LRRK2 -PD. Methods: 218 eyes belonging to 20 iPD, 19 LRRK2 -PD (L2PD), 24 LRRK2 non-manifesting carriers (L2NMC), and 46 controls (HCs). pRNFL, mGCL thickness (squares), and Bruch's membrane opening minimum rim width were evaluated by SD-OCT. In L2NMC, 123 I-ioflupane SPECT (DaT-SPECT) with semi-quantitative analysis was carried out. Results: Compared to HCs, iPD patients showed significant thinning of the temporal (BMO-MRW and pRNFL), superior-temporal (BMO-MRW), inferior-temporal (BMO-MRW), superior-nasal (BMO-MRW) and central sectors (BMO-MRW) (p < 0.05), as well as in five mGCL sectors (p < 0.05). No significant differences were found between the L2PD or L2NMC and HCs. BMO-MRW thickness in its temporal-superior, superior-nasal and middle sectors was influenced by disease duration (p < 0.05) and mGCL thickness in sectors TS1, TS2, TS3, NS1 and NS3 was influenced by UPDRSIII and age (p < 0.05). Conclusion: LRRK2 -PD is distinguished from iPD by absent or less retinal nerve involvement, both in clinical and preclinical stages. Highlights: The peripapillary retinal nerve fiber layer of the retina is thinned in idiopathic PD. In LRRK2 -PD there seems to be minor or absent retinal thinning. OCT might not to be useful to differentiate clinical or asymptomatic LRRK2 -PD from healthy controls.